Development of Notion-assisted e-modules for enhancing mathematical communication in vocational high schools - Sulastri, Yayu Laila; Ahmatika, Deti; Auliya, Selma; Septriani, Anisa; Elsa, Elsa; Khaerunnisa, Najlaa Kania; Sundhari, Rachma (Universitas Sarjanawiyata Tamansiswa, 2024)
The learning process often relies solely on lecture and discussion methods due to the lack of e-module teaching tools that utilize information technology tailored to students' needs and the students' low mathematical communication skills concerning two-variable linear inequalities. This research aims to determine the validity and effectiveness of students' mathematical communication skills after learning with the two-variable linear inequality e-module assisted by Notion. The research method used is Research & Development with the ADDIE design. The data sources in the research include material expert validators, media experts, and students. Data collection techniques involve validation sheets from material experts, media experts, observation of the learning process, feedback questionnaires, and mathematical communication skills tests. Based on the analysis results, it can be concluded that the developed teaching module is valid and highly valid. The average value of mathematical communication skills reached 83.59, classified as medium. Classical learning completeness was 84.37%. Learning completeness for the low class category is 75%, the medium class category is 80.95%, and the high class category is 100%. In conclusion, the Notion-assisted two-variable linear inequality e-module significantly enhances the mathematical communication skills of vocational high school learners, demonstrating its effectiveness and validity as a teaching tool.